Tourism and Inequality in the European Union: Exploring the Determinants of Tourism Spending through a Multivariate Approach - GRZENKOWICZ, Alicja (Journal of Environmental Management and Tourism; Vol 16 No 3 (2025): JEMT, Volume XVI, Issue 3(79), Fall 2025, 2025)
This paper aims to identify and analyze economic, social, and demographic factors influencing tourism expenditures across 26 European Union member states, offering a multidimensional perspective on consumer behavior in tourism. The study uses panel data from 2014 to 2023 obtained from Eurostat, covering all EU countries except Sweden. Variables analyzed include GDP per capita, Gini coefficient, education level, demographic structure, and life satisfaction. A correlation analysis for 2023 explores the relationships between tourism expenditure and selected socio-economic indicators. The findings reveal significant differences in the level and composition of tourism expenditures between higher- and lower-income countries. In wealthier nations, expenditure is linked to income, social inequality, age, and life satisfaction. In less affluent countries, income, age structure, and education play a more prominent role. This study combines traditional economic indicators with social and psychographic determinants, emphasizing the role of quality of life in shaping sustainable tourism behavior. Further research is needed to explore causal relationships and regional patterns affecting tourism expenditure and access, supporting more targeted and effective policy interventions. The findings support the design of inclusive tourism strategies that reflect varying development levels and cultural contexts, promoting regional cohesion and equitable access. Improving access for disadvantaged groups, such as older adults, low-income populations, and people with disabilities, is a key priority amid Europe’s aging society.